Authentic pride regulates runners' training progress. (September 2018) - Gilchrist, Jenna D.; Sabiston, Catherine M.; Conroy, David E.; Atkinson, Michael
Abstract: Objectives: Among both exercisers and athletes, affect provides feedback about progress toward goals and feelings of authentic pride can serve as a barometer of achievement. Low levels of authentic pride may signal that changes in effort or behavior are needed. Prior work has focused on stable individual differences in pride rather than fluctuations in pride as people pursue their goals. The purpose of this study was to test the hypotheses that achievement is associated with authentic pride and that fluctuations in authentic pride predict changes in training behaviors as evidenced by fluctuations in subsequent training progress. Design: This study used a longitudinal design with repeated weekly online diaries and multilevel modelling to test study objectives. Method: Participants training for a long-distance race ( N  = 131, 78% women; M  = 35.4 years) provided weekly self-reports on pride and training progress for seven weeks. Results: Multilevel models indicated that training progress predicted authentic pride at both the within- ( b  = 0.43, p  < .001) and between-person level ( b  = 0.53, p  < .001). When participants reported lower authentic pride than usual on a given week, training progress increased the following week ( b  = −0.31, p  < .001). Conversely, greater authentic pride was associated with greater training progress on average ( b  = 0.21, p  < .001). Conclusions: Consistent with control-process accounts, runners may use their feelings of pride to regulate their behavior. Low feelings of pride can be adaptive for goal striving by signaling when strategies or efforts need to be adjusted. Highlights: Positive emotions are important for goal striving. Training progress was positively associated with feelings of pride. Greater authentic pride was associated with greater training progress, on average. Low authentic pride on a given week was associated with greater training progress the following week. Feelings of authentic pride can be adaptive for goal striving by signaling when strategies or effort need to be adjusted.